ChemInform Abstract: Synthesis and Structure of New Imidazo‐ and Pyrazolo[5, 1‐d][1, 2, 3, 5]thiatriazines Based on the Reaction of Diazoazoles with Acyl Isothiocyanates Controlled by S···O Interaction. Issue 50 (10th December 2013) - Sadchikova, Elena V.; Bakulev, Vasiliy A.; Subbotina, Julia O.; Privalova, Darya L.; Dehaen, Wim; Van Hecke, Kristof; Robeyns, Koen; Van Meervelt, Luc; Mokrushin, Vladimir S.
Abstract Cycloaddition reactions of 5‐diazopyrazoles and 5‐diazoimidazoles with acyl isothiocyanates give thiatriazine derivatives.